Unipampa campus Alegrete: extensão universitária e articulação universidade-comunidade - Dalmolin, Antonio Marcos Teixeira (2014)
This work was developed under the research line School Practice and Public Policy, the Graduate Program in Education, the Federal University of Santa Maria, with the theme of university extension. This, in general, assumes an extension offer perspective, linear, in which are offered to the community results that, oftentimes, have little relation to actual problems of the local/regional community. In this context this research problem emerged: How do the extension projects of the Federal University of Pampa, Campus Alegrete, contemplate the guidelines of the Institutional Project in the relationship between university-society in general, local and regional culture? The overall objective was to examine how the extension projects of the Federal University of Pampa, Campus Alegrete, contemplate the guidelines of the Institutional Project according to the references of Paulo Freire and Latin American Thought in Science, Technology and Society (PLACTS). In terms of methodological rating the research is qualitative, case study type. The corpus analysis was composed of drafts of extension projects registered in UNIPAMPA between the years 2008-2012 and the analysis technique was the Textual Discourse Analysis, made of three stages: unitarization, categorization and communication. The results were synthesized into three interrelated categories, which are: extension offer conception, inseparability Teaching-Research-Extension and University-Society link. The first one showed three trends, representing the extension offer character of most projects, which are: knowledge provision with a focus on dissemination/diffusion of Science-Technology, offering expertise with a focus on courses and training and adjusted offer by social demands. The second category showed three interrelated conditions that, to a greater or lesser extent, hampers effective joint between Education-Research-Extension. They are: the extension offer character associated with the extension, the extension on curriculum and conceptual aspects of the university extension. In the third category three signals were discussed in the research corpus, which may be associated with processes of "redness" on societyuniversity articulation, at UNIPAMPA, Campus Alegrete. They are: extension as knowledge exchange between university-society, social demands identification by extension and extension and social transformation.